PENERAPAN AKUNTANSI SEKTOR PUBLIK DALAN MENCEGAH FRAUD DI ERA DIGITAL - Mulyadi, Nanda Pramayasti; Indrabudiman, Amir (LPPM Universitas Bina Bangsa, 2025)
The ever-evolving technology has a major influence on many aspects of human life, where technology is expected to have a positive impact on the public accounting sector by making it simpler and faster to implement various accounting procedures and produce more accurate data that produces results. One of them is utilized to prevent fraud cases in various sectors, not only the business world but also government. Therefore, the importance of combining public sector accounting combined with technology is considered capable of reducing the phenomenon of fraud growth which has recently become increasingly common. This writing utilizes a literature review to strengthen the results of the discussion with the aim of examining the implementation of public sector accounting as an effort to prevent fraud. The results of the study state that the implementation of technology in public sector accounting is considered necessary to continue to be developed and utilized in order to reduce the number of frauds in Indonesia